Development of an active pulsed radar receiver for a mono-static borehole-radar tool - Woods, Brian Keith (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2003.